Synthesis of Literature on Antioxidant Activity and Safety of Seroja (Nelumbo nucifera Gaertn.) Plant Relative to Pharmacological Potential - Kendrick Mahapurisa; Ferina Angelia; William (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Nelumbo nucifera Gaertn. (Nelumbonaceae), known as the sacred lotus, is widely distributed across Asia and has long been used as food and traditional medicine, although its utilization in Indonesia remains largely ornamental. Interest in its antioxidant potential and its role as a source of bioactive compounds has increased. This review aims to systematically summarize in vitro and in vivo evidence on the antioxidant activity of N. nucifera, identify key plant parts and active compounds, compare extraction and assay methods, and evaluate preclinical bioactivity and safety. Literature searches in Google Scholar, NCBI, and PubMed using the keywords